2022
DOI: 10.53808/kus.2017.14.1and2.1625-s
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Pornography Among Students at Educational Institutions in Khulna City Corporation, Southwest Bangladesh

Abstract: This study aimed at exploring the underlying factors of exposure to pornography among the students at educational institutions in Khulna City of Bangladesh. Following survey research design, a sample of 304 students (200 male and 104 female) were selected randomly from three educational institutions and data were collected by administering a semi-structured interview schedule. Findings reveal that majority of the students (about 81%), male in particular, are exposed to pornography before sixteen years of age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…In contrast, students under 21 may have been spending more time with their peers in offline activities, minimizing online engagement and reducing exposure to pornography ( 36 ). The findings of the current study complement the work of Golder et al ( 27 ) who noted a higher exposure to pornography among older students, while Chowdhury et al ( 28 ) found greater exposure among younger students than among their older counterparts.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In contrast, students under 21 may have been spending more time with their peers in offline activities, minimizing online engagement and reducing exposure to pornography ( 36 ). The findings of the current study complement the work of Golder et al ( 27 ) who noted a higher exposure to pornography among older students, while Chowdhury et al ( 28 ) found greater exposure among younger students than among their older counterparts.…”
Section: Discussionsupporting
confidence: 88%
“…Vera Cruz ( 41 ), for example, found that men with frequent exposure to pornography, especially young men, were more likely to engage in sadistic sexual behavior toward their female partners, largely due to their sexual fantasies. However, the findings of this study supports that of Golder et al ( 27 ), who noted that higher religiosity reduces the possibility of pornography exposure; Mamun et al ( 26 ), in contrast, found no influence of religious and moral values on pornography consumption, because strong religiosity may not always translate into specific activities prohibited by religion, such as pornography use ( 42 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation